Conceptual change: Still a powerful framework for improving the practice of science instruction - Duit, R.; Treagust, David (2012)
© Springer Science+Business Media B.V. 2012. Conceptual change perspectives of teaching and learning processes in science, and also in various other content domains, have played a significant role in research on teaching and learning as well as in instructional design since the late 1970s. Research findings indicate that conceptual change-oriented instructional design may in fact be suited to improve the development of student cognitive and affective outcomes. However, such improvements are only to be expected if conceptual change perspectives are further developed — far beyond the ‘classical’ perspective introduced in the 1980s. It is argued that there are the following challenges for future research and development: Research on conceptual change needs to take into account multiple epistemological perspectives of teaching and learning, to give equal attention to cognitive and affective student variables, to embed conceptual change approaches into inclusive models of instructional planning, to determine the necessary and sufficient evidence for identifying conceptual change and to bring successful conceptual change teaching approaches to normal classes.